A WSSL Implementation for Critical Cyber-Physical Systems Applications - Rocha, Márcia (2023)
The advancements in wireless communication technologies have enabled unprecedented pervasiveness and ubiquity of Cyber-Physical Systems (CPS). Such technologies can now empower true Systemsof-Systems, which cooperate to achieve more complex and efficient functionalities. However, for CPS applications to become a reality, safety and security must be guaranteed, particularly in critical systems, since they rely on open communication systems prone to intentional and non-intentional interferences. We propose designing a Wireless Safety and Security Layer (WSSL) architecture to be implemented in critical CPS applications to address these issues. WSSL increases the reliability of these critical communications by enabling the detection of communication errors. Furthermore, it increases the CPS security using a message signature process that uniquely identifies the sender. So, we present the WSSL architecture and its implementation over an MQTT protocol. We prove that WSSL does not significantly increase the system transmission costs and demonstrate its capability to ensure safety and security, allowing it to be used in any general or critical CPS.